Mediation Principles in the Civil Society and Features of Their Application in the Educational Environment of Ukraine - Sheremet, Anzhelika; Blashchuk, Tetiana; Ishchuk, Serhii (Journal of Education Culture and Society, 2022)
Aim. The main purpose of research presented in this article is to analyse mediation principles as an alternative way of dispute resolution and features of their application in the educational environment of Ukraine. For which purpose it was necessary to perform the following tasks: - the concept and role of mediation principles were studied; - certain types of mediation principles were defined; - the essence and significance of the most important mediation principles were revealed; - and the application of mediation principles in Ukraine was clarified. In Ukraine, civil society institutions have been trying on their own to introduce and promote mediation as a way of alternative dispute resolution. However, systemic problems of access to justice require finding other ways to resolve conflict situations. Mediation becomes especially relevant in the context of COVID-19 coronavirus pandemic, when access to the court system is limited.Methods. The study is based on the analysis of enacted regulations and their comparison in different countries, as well as information obtained from the study of literature, including works by authors of both legal and other social sciences where mediation is used as a means of compromise, including psychology, medicine, ecology, along with the use of tools and comments specific to the study of law. To study the prospects and effective application of mediation principles in the educational environment, sociological surveys of various participants of the educational process were conducted.Results. The results of study showed that certain types of mediation principles are applied in different countries taking into account the peculiarities of national legal systems. Notwithstanding, such principles as the rule of law, the principle of equality (equal rights) of the parties, the principle of voluntariness, confidentiality and mediator behaviour (independence and impartiality, trust and justice) are applied in most of the studied national models of mediation, consequently they can be called fundamental. The survey results have revealed the readiness of the educational environment to introduce mediation as a tool for resolving conflicts in the educational environment.  In Ukraine, the draft law “On Mediation” defines general principles of mediation; however, the problem is insufficiently clear criteria for disputes that cannot be transferred to mediation. In addition, the principle of the rule of law should be defined as one of the fundamental principles of mediation.Conclusions. The specifics of the implementation of mediation principles in Ukraine and their correlation with the principles of the judicial process require further research.